Jeremy Rifkin about the consequences of the revolution of biotechnology. A criticism of the „biotechnology century” - Słoniowska, Anna (Studia Ecologiae et Bioethicae, 2014)
Nowadays we are entering a new period in our history. It is an era of great computers, new technologies, and genetic engineering. Most people look to the future with hope, but not Jeremy Rifkin, the American economist, and critic of modern civilization. He has called this period 'The Biotech Century'. In his opinion, humanity is treading on thin ice. He believes, that biotechnology brings more disadvantages than advantages. He is trying to convince us that scientists are playing God in their laboratories. They often invent great things like new medicines or therapies. However, Rifkin also points to the other side of the coin. Firstly, there is no way of predicting the effects of biotechnology. Secondly, the human genetic code will be used for commercial purposes. Our genes will be on the market, like any other product in the supermarket. And thirdly, Riffkin warns against the return of eugenics. But this new eugenic will be more powerful, and much more dangerous.